IMPLEMENTASI MODEL INQUIRI SEBAGAI UPAYA MENINGKATKAN BERPIKIR KRITIS SISWA KELAS XI IPS DI SMA NEGERI 7 YOGYAKARTA PADA MATA PELAJARAN SOSIOLOGI - Purwanto, Edy; Ramly, Linda Nur; Nugraha, Andi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract The aim of the research is to improve the students' critical thinking. The method employed is classroom action research by implementing inquiry learning. This action research consists of three cycles, each of which includes the steps of planning, acting, observing, and reflecting. The subjects of the research are the grade XI students of State Senior High School 7 YOGYAKARTA. The findings have shown that the students learn more actively and creatively.